Amplificação isotérmica de DNA mediada por loop (LAMP) em microchip de poliéster-toner - Oliveira, Kezia Gomes de (2016)
The several advantages of miniaturization of DNA amplification and coupling with sample preparation and detection steps on the same chip are well known. Currently, most miniaturized systems for nucleic acids analysis are based on polymerase chain reaction (PCR). PCR amplification requires precise temperature control, switching between heating and cooling solution in three specific temperatures. Therefore, the adaptation of PCR for microchip is relatively complex and presents some limitations particularly for use in remote locations. Without the need for heating cycles, isothermal microsystems for DNA amplification can be designed to be simple and low energy consumption and hence can overlap the portable PCR detection systems. The loop-mediated isothermal amplification (LAMP) is a novel technique which has emerged as a simple and fast tool for DNA amplification which can be used for the detection and identification of several pathogens. The LAMP using Bst DNA polymerase enzyme which is an enzyme having strand displacement activity and uses a set of four primers designed from six individual segments of the sequence to be amplified. In this study, we developed a simple and rapid LAMP reaction for the E. coli malB gene amplification in the reaction was thermally controlled with a thermoblock for 60 minutes at 66 ° C. The PeT microdevices demonstrated compatibility with all reagents used in the LAMP and the success of the isothermal amplification was observed by agarose gel electrophoresis, yielding detectable amount amplicons as few as starting with 1 copy of DNA. Moreover, the success of the nucleic acid amplification reaction was evaluated by visual detection of the amplicons in the microchip by the use of fluorescent DNA intercalators, which yielded fluorescence in positive reactions. The LAMP in PeT microdevice is a simple and inexpensive method, that allowed a rapid detection (62 minutes) of E. coli. Because of simple operation and without the need for sophisticated instrumentation, LAMP held in microchip PeT has proven to be a valuable tool for molecular diagnostics, with great potential for applications in point-of-care.